2015
DOI: 10.1007/s00395-015-0483-8
|View full text |Cite
|
Sign up to set email alerts
|

MCP-1-induced protein attenuates post-infarct cardiac remodeling and dysfunction through mitigating NF-κB activation and suppressing inflammation-associated microRNA expression

Abstract: MCP-1-induced protein (MCPIP, also known as ZC3H12A) has recently been uncovered to act as a negative regulator of inflammation. Expression of MCPIP was elevated in the ventricular myocardium of patients with ischemic heart failure. However, the role of MCPIP in the development of post-infarct cardiac inflammation and remodeling is unknown. The objective of the present study was to investigate whether MCPIP exerts an inhibitory effect on the cardiac inflammatory response and adverse remodeling after myocardial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 61 publications
(143 reference statements)
3
42
0
Order By: Relevance
“…various biological activities, including mediated inflammatory response and immune response (Chen and Zhou, 2015). MCP-1 is one of the most important cell factors in the chemotaxis of monocytes/macrophages to renal tissue, which lead to a large number of monocytes/macrophages in the lesion (Donadelli et al, 2000;Niu et al, 2015). The activation of NF-kB and downstream release of IL-6 and MCP-1 were found in our study, emphasizing the vital role of inflammation in CIN.…”
Section: Discussionmentioning
confidence: 46%
“…various biological activities, including mediated inflammatory response and immune response (Chen and Zhou, 2015). MCP-1 is one of the most important cell factors in the chemotaxis of monocytes/macrophages to renal tissue, which lead to a large number of monocytes/macrophages in the lesion (Donadelli et al, 2000;Niu et al, 2015). The activation of NF-kB and downstream release of IL-6 and MCP-1 were found in our study, emphasizing the vital role of inflammation in CIN.…”
Section: Discussionmentioning
confidence: 46%
“…Cardiomyocyte-targeted expression of MCPIP protected against endotoxin-induced myocardial inflammation and dysfunction 12 . The level of MCPIP was also significantly increased in the murine heart after ligation of left coronary artery 13 . Mice with cardiomyocytetargeted expression of MCPIP showed improved survival, decreased cardiac hypertrophy, lower fibrosis and scar formation as well as better left ventricular function after myocardial infarction 13 .…”
Section: Mcpip In Preconditioning Of the Heartmentioning
confidence: 88%
“…The level of MCPIP was also significantly increased in the murine heart after ligation of left coronary artery 13 . Mice with cardiomyocytetargeted expression of MCPIP showed improved survival, decreased cardiac hypertrophy, lower fibrosis and scar formation as well as better left ventricular function after myocardial infarction 13 . MCPIP overexpressing murine heart also showed decreased monocytic cell infiltration and inflammatory cytokine expression as well as lower caspase 3/7 activities and apoptotic cell death compared to wild type mice 13 .These protective effects of MCPIP probably involve its ability to inhibit NF-κB activation as the MCPIP expressing murine hearts showed lower NF-κB signaling 12,13 .…”
Section: Mcpip In Preconditioning Of the Heartmentioning
confidence: 88%
See 1 more Smart Citation
“…Inflammatory cytokines and myocardial fibrosis form a complex regulatory network and the levels of inflammatory factors are closely linked to the degree of cardiac fibrosis (1,2). Therefore, the protective effect of hesperetin may be associated with the following mechanisms: First, hesperetin significantly inhibited NF-κB signaling pathway activation; NF-κB is a key regulator of the inflammatory response, whose activation promotes inflammation and induces the production of pro-inflammatory cytokines, including TNF-α, IL-1β and IL-6, and it has been demonstrated that pro-inflammatory cytokines exert their effects on cardiomyocytes through activating NF-κB after MI (23,24). Furthermore, hesperetin inhibited cardiac fibrosis induced by inflammatory factors; inflammatory cytokines not only stimulate the synthesis of extracellular matrix in cardiac fibroblasts, but also reduce the number of cardiomyocytes by causing cardiac necrosis and apoptosis after MI, resulting in cardiac fibrosis (25).…”
Section: Discussionmentioning
confidence: 99%